Kompetensi dan Motivasi Kerja Dalam Meningkatkan Kinerja Pegawai di RSUD R. Syamsudin, SH. Kota Sukabumi - Tarjono; Ridwan Heryawan; Dadang Sadili (LPPM Sekolah Tinggi Ilmu Ekonomi PGRI Sukabumi, 2021)
This research aims to analyze the impact of competence and work motivation on employee performance at RSUD R. Syamsudin, SH. Sukabumi City. Researchers used a quantitative approach with associative and questionnaire methods as a means of data collection. The population is all employees at R. Syamsudin Hospital, SH. The City of Sukabumi has a total of 1,446 employees, sampling using the slovin formula with an error degree of 10%, so the sample is 94 employees, and the sampling technique is proportional stratification random sampling technique. The data analysis technique used is multiple linear regression analysis and so on with multivariate regression analysis. The results, both independently and simultaneously, employee competence and work motivation have an impact on employee performance at R. Syamsudin, SH Hospital. Sukabumi City; (5) There is a positive and significant effect of work motivation on employee performance at RSUD R. Syamsudin, SH. Sukabumi City.